1996
DOI: 10.1086/192373
|View full text |Cite
|
Sign up to set email alerts
|

Abundances at High Redshifts: The Chemical Enrichment History OF

Abstract: We study the elemental abundances of C, N, O, Al, Si, S, Cr, Mn, Fe, Ni, and Zn in a sample of 14 damped Lyα systems (galaxies) with H I column density N (H I)≥ 10 20 cm −2 , using high quality spectra of quasars obtained with the 10m Keck telescope. To ensure accuracy, only weak, unsaturated absorption lines are used to derive ion column densities and elemental abundances. Combining these abundance measurements with similar measurements in the literature, we investigate the chemical evolution of damped Lyα ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
462
9
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 377 publications
(519 citation statements)
references
References 78 publications
47
462
9
1
Order By: Relevance
“…It may well be indeed, that most of the lines of sight to quasars intercept various parts of (proto)galactic disks. This conclusion is opposite to the one reached in [15], which was based on a comparison of the data to the age-metallicity relationship of the LD only. Notice that for geometrical reasons, the probability of detecting outer disk regions is higher, favouring systematically lower abundances than those spanned during the LD history.…”
Section: Implications For "Cosl\tiic Chemical Evolution"contrasting
confidence: 90%
See 2 more Smart Citations
“…It may well be indeed, that most of the lines of sight to quasars intercept various parts of (proto)galactic disks. This conclusion is opposite to the one reached in [15], which was based on a comparison of the data to the age-metallicity relationship of the LD only. Notice that for geometrical reasons, the probability of detecting outer disk regions is higher, favouring systematically lower abundances than those spanned during the LD history.…”
Section: Implications For "Cosl\tiic Chemical Evolution"contrasting
confidence: 90%
“…should account for the discrepancy between theory (solid line) and observations (data from [11]) b) Evolution of gas and stars; data for HI gas density from [29]. c) The evolution of Zn/H in various regions of spiral disks (only three are shown here, corresponding to those on the left) brackets well the observed abundances of Zn/H in Lyo absorbers (data from [18,15]); those systems may well be (proto)galactic disks. d) The corresponding evolution of D shows that considerable depletion may take place in the inner disk regions, but only at low redshifts; abundances measured at high redshifts should be close to the primordial value.…”
Section: Implications For "Cosl\tiic Chemical Evolution"mentioning
confidence: 60%
See 1 more Smart Citation
“…However, it is also clear that stars less massive than about 5M produce and expel carbon as well (van den Hoek & Groenewegen 1997;Marigo et al 1996Marigo et al , 1998Henry et al 2000), and the relative significance of massive and intermediate mass stars has not been established. Lu et al (1996; and with the observed abundances of blue compact galaxies found by Izotov & Thuan (1999) at very low metallicity. Then, at 12+log(O/H)>8 N/O turns upward and rises steeply.…”
Section: Datasupporting
confidence: 84%
“…Filled circles are stellar data from . The circle indicates the position of the Orion Nebula (Esteban et al 1998), the large S shows the position of the sun (Grevesse et al 1996), and the L symbols at extremely low oxygen show upper limits for two high redshift damped Lyman-α objects in Lu et al (1996). Progenitor star metallicities are identified by line types, as indicated in the legend.…”
Section: Discussionmentioning
confidence: 99%